Estimation of the Equilibrium Real Exchange Rate for South Africa - MacDonald, Ronald (IMF Working Papers; Working Paper ;, 2003)
Based on the Johansen cointegration estimation methodology, much of the long-run behavior of the real effective exchange rate of South Africa can be explained by real interest rate differentials, GDP per capita (both relative to trading partners), real commodity prices, trade openness, the fiscal balance, and the extent of net foreign assets. On the basis of these fundamentals, the real exchange rate in early 2002 was found to be significantly more depreciated with respect to the estimated equilibrium level. The half-life of the deviation of the real exchange rate from the estimated equilibrium one was found to be somewhat more than two years.